Mitogenomic architecture and evolution of the soil ciliates Colpoda - Yuanyuan Zhang; Haichao Li; Yaohai Wang; Mu Nie; Kexin Zhang; Jiao Pan; Yu Zhang; Zhiqiang Ye; Rebecca A. Zufall; Michael Lynch; Hongan Long (mSystems, 2024)
ABSTRACTColpoda are cosmopolitan unicellular eukaryotes primarily inhabiting soil and benefiting plant growth, but they remain one of the least understood taxa in genetics and genomics within the realm of ciliated protozoa. Here, we investigate the architecture of de novo assembled mitogenomes of six Colpoda species, using long-read sequencing and involving 36 newly isolated natural strains in total. The mitogenome sizes span from 43 to 63 kbp and typically contain 28–33 protein-coding genes. They possess a linear structure with variable telomeres and central repeats, with one Colpoda elliotti strain isolated from Tibet harboring the longest telomeres among all studied ciliates. Phylogenomic analyses reveal that Colpoda species started to diverge more than 326 million years ago, eventually evolving into two distinct groups. Collinearity analyses also reveal significant genomic divergences and a lack of long collinear blocks. One of the most notable features is the exceptionally high level of gene rearrangements between mitochondrial genomes of different Colpoda species, dominated by gene loss events. Population-level mitogenomic analysis on natural strains also demonstrates high sequence divergence, regardless of geographic distance, but the gene order remains highly conserved within species, offering a new species identification criterion for Colpoda species. Furthermore, we identified underlying heteroplasmic sites in the majority of strains of three Colpoda species, albeit without a discernible recombination signal to account for this heteroplasmy. This comprehensive study systematically unveils the mitogenomic structure and evolution of these ancient and ecologically significant Colpoda ciliates, thus laying the groundwork for a deeper understanding of the evolution of unicellular eukaryotes.IMPORTANCEColpoda, one of the most widespread ciliated protozoa in soil, are poorly understood in regard to their genetics and evolution. Our research revealed extreme mitochondrial gene rearrangements dominated by gene loss events, potentially leading to the streamlining of Colpoda mitogenomes. Surprisingly, while interspecific rearrangements abound, our population-level mitogenomic study revealed a conserved gene order within species, offering a potential new identification criterion. Phylogenomic analysis traced their lineage over 326 million years, revealing two distinct groups. Substantial genomic divergence might be associated with the lack of extended collinear blocks and relaxed purifying selection. This study systematically reveals Colpoda ciliate mitogenome structures and evolution, providing insights into the survival and evolution of these vital soil microorganisms.